MARKETING STRATEGY ANALYSIS OF PONDOK GEDE TEA STORE - Moh Wahib (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2023)
Pondok Gede Tea Shop, a business operating in the beverage sector, must consider ensuring its business continuity amidst intense competition. According to information provided by the shop owner, the annual turnover is perceived to follow a linear trend. Although the current turnover adequately covers operational costs, the shop aims to augment its turnover through increased tea sales. This research employs a descriptive approach, utilizing data collected via semi-structured interviews. The study's outcomes, based on SAP and ETOP analyses, suggest an appropriate corporate strategy derived from the SWOT matrix: an investment strategy. Specifically, this involves short-term investments with subsequent benefits anticipated in the future.